Endothelial Dysfunction and Vascular Preconditioning - R. Rastaldo (Journal of Biological Research, 2003)
The prolonged occlusion of a coronary artery followed by reperfusion causes deleterious effects known as “ischemiareperfusion injuries”. In fact, these injuries,which affect both myocardium and coronary endothelium, initiate during ischemia and worsen during reperfusion.Thus, although myocardial infarction is the necrosis occurring as a consequence of the ischemia, its size can increase with reperfusion.Usually two hours of reperfusion are sufficient to induce a noticeable increase in size of the infarct area. In addition to necrosis, also myocardial stunning and arrhythmias are features of the damage. [...]